1986
DOI: 10.1055/s-2008-1025738
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ventilatory Performance of Athletes Using the Maximal Expiratory Flow-Volume Curve

Abstract: We carried out a maximum expiratory flow-volume curve (MEFV) and a spirometric recording with 67 athletes of different ages (15-27 years) and disciplines (rowers, kayakists, cyclists, swimmers) and with 20 adult and 13 adolescent nonathletic controls of matching ages. These recordings were repeated, with athletes only, after 6-10 months of training. Significant differences between the groups of adult athletes and the controls were observed for some parameters, the most discriminating of which were, in order, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
7
0
2
Order By: Relevance
“…Studies comparing respiratory function among people engaged in different sports found that female and male swimmers have higher VC and FVC than athletes of other sports, as well as sedentary controls (Cordain et al, 1990;Kesavachandran, Nair, & Shashidhar, 2001;Phervani, Desai, & Solepure, 1989). It was found that flow rates such as PEF, MEF50, and MEF 25 are higher for male and female swimmers than others, and the swimmers showed increased conductivity of large and small airways and higher speeds of respiratory-muscle contraction (Bertholon et al, 1986;Phervani et al). Bertholon et al found that FEV1 is higher in athletes than sedentary controls.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Studies comparing respiratory function among people engaged in different sports found that female and male swimmers have higher VC and FVC than athletes of other sports, as well as sedentary controls (Cordain et al, 1990;Kesavachandran, Nair, & Shashidhar, 2001;Phervani, Desai, & Solepure, 1989). It was found that flow rates such as PEF, MEF50, and MEF 25 are higher for male and female swimmers than others, and the swimmers showed increased conductivity of large and small airways and higher speeds of respiratory-muscle contraction (Bertholon et al, 1986;Phervani et al). Bertholon et al found that FEV1 is higher in athletes than sedentary controls.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are supported by the investigations of other authors (Kesavachandran et al; Phervani et al). Higher FEV1 for swimmers indicates higher conductivity of large airways as a result of increased VC, which allows greater airflow through the airways during the first second of expiration and inspiration (Bertholon et al;Wells, Plyley, Thomas, Goodman, & Duffin, 2005). Higher FIV1 indicates important adaptations of the respiratory system that enable a swimmer to inhale more air during a short time while swimming.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Os valores obtidos podem estar diminuídos em relação ao previsto quando o paciente apresenta doenças neuromusculares, doença pulmonar obstrutiva crônica (DPOC), fibrose cística e insuficiência cardíaca congestiva, podendo ser também um indicativo de má nutrição, doenças endócrinas associadas ao colágeno e uma das consequências de um longo tratamento com medicamentos à base de corticoesteroides (4). Contudo, os valores das mensurações podem ser maiores em indivíduos sadios que se submetem regularmente a treinamento físico (16,17).…”
Section: Introductionunclassified